(untitled) (Global Journal of Medical Research, 2024)
Rokitansky - K ster-Hauser syndrome MRKH is characterized by agenesis or aplasia of the uterus and upper part of the vagina and is considered the second most common cause of primary amenorrhea The psychological repercussions are significant and are directly related to sexual and reproductive health This work reports the case of a teenager with MRKH and reviews the syndrome and the main factors that impact mental health Case Description Adolescent 14 years old female absence of menarche sexual life not initiated Tanner M5P5 Pelvic ultrasound with hypoplastic uterus magnetic resonance imaging of the pelvis with non-individualized uterus unidentified vagina and ovaries with normal topography and morphology Diagnosed with MRKH and has no desire to perform vaginal dilation He has difficulty talking about the syndrome and aspects of his sexual life She appeared sad and felt inadequate especially after her father told her she was less of a woman Discussion MRKH is the second most common cause of primary amenorrhea and its psychosocial impact is relevant Historically the uterus is described as primordial in female identity and menarche is an important milestone in puberty in girls People with the syndrome tend to present more anxious and depressive symptoms image disturbances influencing self-esteem and identity construction Conclusion The diagnosis of MRKH involves several factors that go beyond anatomical changes Therefore it is essential to include emotional aspects in the clinical approach aiming to improve sexual reproductive and mental health and above all the quality of life of these people